Governance and Sustainability in the Local Context: An Interpretative Study of BUMDes in Banten - Faidurrizal; Leo Agustino; Rina Yulianti (LP2M IAIN Palopo, 2025)
Village-Owned Enterprises (BUMDes) in Indonesia are mandated to implement good governance principles and advance sustainable development. However, understanding how governance and sustainability operate in local contexts remains limited. This qualitative interpretive study examined governance and sustainability practices across five purposively selected BUMDes in Banten Province. The research employed multiple case study design with data collected through ten semi-structured in-depth interviews with BUMDes managers, village officials, and community leaders, combined with document analysis of strategic plans, governance reports, and financial records from 2022 through 2025. Interview and documentary data were analyzed using thematic analysis methodology employing systematic coding, theme development, data triangulation, and reflexive interpretation to ensure analytical credibility and dependability. The findings reveal four critical themes. First, BUMDes governance operates through dynamic duality where formal structures provide legitimacy while informal networks grounded in kinship relations exert preponderant influence over actual decision-making. Second, sustainability is interpreted adaptively, emphasizing short-term economic survival despite embedded social and environmental commitments rooted in local values. Third, persistent tensions exist between organizational efficiency imperatives and stakeholder inclusivity, resulting in marginalization of women and youth. Fourth, social capital encompassing trust and community cohesion functions as critical institutional buffer enabling organizational resilience during crises. The research concludes that governance and sustainability in BUMDes represent ongoing navigation processes between competing institutional imperatives rather than matters of simple regulatory compliance. Governance requires contextually adaptive approaches recognizing informal mechanisms as legitimate institutional contributions deserving deliberate strengthening. Support programs should emphasize social capital cultivation alongside technical skill development and facilitate dialogue between formal and informal governance systems to enhance organizational capacity and institutional sustainability